Broadcast data delivery special considerations in underwater acoustic sensor networks - Плахотный, Н. В.; Тихановский, В. В.; Кебкал, А. Г. (Problems of Informatization and Control, 2009)
The reliable broadcast data communication task is examined in a submarine acoustic sensor network, existing broadcast information delivery protocols and proper access methods, multiple access methods and the multicast encoding problem are analyzed